Quality of life in older immigrant adults on hemodialysis - Demba Keita (PLoS ONE, 2025)
Background In the United States (U.S.), over 34% of individuals with Chronic kidney disease (CKD) are aged 65 or older. Understanding the quality of life (QoL) in this population is essential. While there has been research on the experiences of U.S.-born older adults on hemodialysis, there is limited data on the experiences of older immigrant adults with CKD. Purpose This study aims to explore the perceived QoL of older immigrant adults living with stage 5 CKD, with a focus on how the disease impacts their cultural beliefs, practices, and overall well-being. Methods A qualitative, basic interpretive approach was employed to capture the lived experiences of older immigrant adults undergoing hemodialysis. Participants were selected based on predefined inclusion and exclusion criteria. The Short Blessed Test (SBT) was used to screen for cognitive impairment. Participants were recruited in the Mid-Hudson Valley Region of New York. Data were collected through semi-structured interviews. Thematic analysis was applied to the data to identify key themes and patterns in the participants’ experiences. Results The findings revealed that the QoL of older immigrant adults on hemodialysis is shaped by complex interactions between family and social support, cultural and religious practices, balancing independence and dependence, health and illness perceptions, life adjustments to hemodialysis, emotional responses, and immigration adjustment. Participants highlighted the significance of spiritual and cultural beliefs in maintaining resilience and managing the emotional stress of the disease. Conclusion The study underscores the need for culturally competent care that integrates social, emotional, and spiritual support to improve the QoL of older immigrant adults on hemodialysis. The findings suggest that CKD care must extend beyond biomedical factors to include sociocultural and spiritual dimensions. The results emphasize the importance of holistic healthcare approaches that respect cultural values and provide support systems to enhance the QoL of this vulnerable group.